CAPACITY BUILDING OF COMMUNITY PROTECTION UNITS IN FACING THE 2024 SIMULTANEOUS GENERAL ELECTIONS IN KARANG BINDU VILLAGE, RAMBANG KAPAK TENGAH DISTRICT, PRABUMULIH CITY, SOUTH SUMATERA PROVINCE - Alfajri, Rahmad; Batubara, Yusi Eva (Jurnal Tatapamong, 2024)
The Community Protection Unit (Satuan Perlindungan Masyarakat/Satlinmas) has a task plays an important role in maintaining public order and security during the general elections to ensure the smooth running of the democratic process. Satlinmas units in Indonesia, including in Karang Bindu Village, face challenges in the simultaneous elections, such as a lack of understanding of their roles and responsibilities, lack of training and knowledge about the election process, and lack of adequate resources. This research aims to identify and analyze these problems so that the capacity of the Satlinmas can be increased in facing the simultaneous elections in Karang Bindu Village. This research used descriptive qualitative method with an inductive approach. The data were collected through observation, interviews, and documentation, and then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The research showed that the capacity building of Satlinmas in facing the 2024 simultaneous general elections in Karang Bindu Village has not been optimal. Keywords: Capacity Building; Community Protection Unit; General Election.